IMPLEMENTATION OF THE SCRAMBLE METHOD IN OVERCOMING BEGINNING READING DIFFICULTIES IN CLASS 1 PRIMARY SCHOOL (SD) STUDENTS - Fauzan, Ahmat; ., Arsil; Noviyanti, Silvina (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
ABSTRACT Reading skills are one of the basic skills for students to be able to find out information during the learning process. It is known that in Class I SDN 111/I Muara Bulian, based on observations, students have initial reading ability with a percentage of 31% (low). This research aims to determine the improvement in students' initial reading skills through the scramble method in Indonesian language subjects in class I at SDN 111/I Muara Bulian. This research is classroom action research (PTK) which consists of two cycles, where the data taken is in the form of observation data through observation sheets observing students' initial reading abilities and teacher observations using the scramble method and documentation. This research was carried out in 4 stages, namely planning, implementation, observation and reflection. The results of this research show an increase in students' learning activeness in the first cycle, the percentage of learning activeness was 65%, then in the second cycle the percentage increased to 98% with a very good category (A). Based on the results obtained, it can be concluded that the students' initial reading ability using the Scramble Method in Indonesian language subjects in class 1 of SDN 111/I Muara Bulian was successful in being improved.